1991
DOI: 10.3109/17453679108994489
|View full text |Cite
|
Sign up to set email alerts
|

Tibial periosteal reactions in soldiers: A scintigraphic study of 29 cases of lower leg pain

Abstract: Twenty-two soldiers with tibial pain along the posteromedial tibial border (29 painful tibias) entered the study. The tibias were evaluated using radiographs and scintigraphs. Follow-up scintigraphs of 12 tibias were performed. The scintigraphic lesions were classified as Stages 0-V depending on the percentage of bone thickness involved. No attempts were made to differentiate between shin splints and stress fractures. Twenty-four symptomatic lesions and five asymptomatic lesions were found by scintigraphy. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 3 publications
0
12
0
2
Order By: Relevance
“…Therefore, patients with shin splints or tibial stress fractures require different treatment methods and periods. Nielsen et al 16 think the term stress fracture should be used only for patients who have an intensive abnormal finding on bone scintigraphs and callus formation as seen on radiographs taken at followup. Plain radiographs in patients with stress fractures show periosteal new bone formation in the late phase.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, patients with shin splints or tibial stress fractures require different treatment methods and periods. Nielsen et al 16 think the term stress fracture should be used only for patients who have an intensive abnormal finding on bone scintigraphs and callus formation as seen on radiographs taken at followup. Plain radiographs in patients with stress fractures show periosteal new bone formation in the late phase.…”
Section: Discussionmentioning
confidence: 98%
“…12 Some authors reported that 20-40% of the lesions seen on scintigraphs were asymptomatic. 16,25 It is difficult to differentiate shin splints from stress fractures in the early phase with a bone scan. 14 Examination with a bone scan is more invasive than MRI.…”
Section: Diagnosis Mri Scansmentioning
confidence: 99%
“…In the diagnosis of a stress‐related injury to bone, radiography has been used as the primary imaging tool. In the early stages of these injuries, the sensitivity of radiography may be as low as 10%, and 30–70% at follow‐up (5, 12, 15, 17, 18). So far, the diagnosis has often been based on bone scintigraphy, which is regarded as the gold standard (1).…”
mentioning
confidence: 99%
“…Conventional radiography has been the primary examination modality used in the assessment of a stress‐related bone injury. Unfortunately, the sensitivity of plain film radiography is poor (6, 8), and it has often been necessary to confirm the diagnosis with scintigraphy which has been used as the gold standard. Recently, the diagnostic usefulness of MR imaging has been verified.…”
mentioning
confidence: 99%